Green banking unveiled: insights into student perspectives on sustainable finance / Liyana Ab Rahman ... [et al.] - Ab Rahman, Liyana; Mohamad, Maslinawati; Shamsudin, Siti Marlia; Roslan, Faros Faizdnor; Alwi, Fatimah (Universiti Teknologi MARA, Kedah, 2023)
The serious environmental risks caused by climate change and carbon emissions have prompted a pressing demand to transition from current practices to more environmentally friendly approaches. Given this urgency, the banking industry must embrace green banking practices to mitigate risks and ensure its stability and resilience as a financial provider. Thus, this study aims to investigate the perceptions of students regarding green banking practices. A survey has been distributed among the students to understand the awareness, understanding, and attitudes of students toward environmentally friendly banking initiatives. The finding reveals that the students are aware of the existence of green banking products, but they have little knowledge of the concept of green banking, which signifies that there is a need to create awareness among the younger generation. Therefore, the proposed Green Banking Index (GBI) application is needed to enhance the understanding of green banking and serves as a comprehensive tool for assessing the bank's green practices. The GBI enables the bank to contribute meaningfully to global efforts to combat climate change by prioritizing sustainability and responding to external stakeholder needs.